Comparative Study of the Role of BUMN and the Private Sector in Empowering Digital-based MSMEs in Pangandaran Regency - Latifah, Leni Lenza; Rosyadi, Slamet; Indiahono, Dwiyanto (Journal of Social and Policy Issues, 2025)
The digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in Pangandaran Regency faces several challenges, including limited technological understanding, market access constraints, and financial limitations. To address these challenges, state-owned enterprises (BUMN) and private sector entities have initiated training and coaching programs to empower digital-based MSMEs. However, comparative studies on the effectiveness of these initiatives remain limited. This study aims to (1) assess the impact of training and coaching on the performance of MSMEs supported by BUMN, (2) evaluate the impact of similar programs on MSMEs assisted by the private sector, and (3) analyze the differences in their effectiveness. Employing a descriptive comparative method with a quantitative approach, this study surveyed two MSME groups: those assisted by BUMN and those supported by private enterprises. The findings indicate that training programs conducted by BUMN significantly enhance MSME performance, while private sector training has a positive but statistically insignificant impact. Conversely, coaching activities provided by private companies exhibit a stronger influence on MSME performance compared to BUMN. Although differences exist between the two groups, they are not statistically significant. These findings highlight the need for optimizing training and coaching methodologies across sectors to maximize MSME empowerment. Future research should explore additional influencing factors and incorporate qualitative approaches for deeper insights.